The Relationship Between Exclusive Breastfeeding and The Incidence of Pneumonia Among Toddlers At Padasuka Health Center, Bandung City, in 2024 - Metha Solihati Rayuna; Amelia Putri; Hanny Yuli Andini (Lembaga Pengembangan Kinerja Dosen, 2025)
Pneumonia is one of the leading causes of death among toddlers in Indonesia. One effective preventive measure is providing exclusive breastfeeding during the first six months of life. This study aims to determine the relationship between exclusive breastfeeding and the incidence of pneumonia among toddlers at the Padasuka Health Center, Bandung City, in 2024. This research employed an analytical quantitative method with a cross-sectional approach and a total sampling technique involving 200 toddlers recorded as having pneumonia based on medical records and IMCI register books. The results showed that 68.5% of toddlers received exclusive breastfeeding, 76.5% experienced mild pneumonia, and 23.5% had severe pneumonia. The Chi-Square test yielded a p-value of 0.001, indicating a significant relationship between exclusive breastfeeding and the severity of pneumonia. Toddlers who did not receive exclusive breastfeeding had a higher risk of developing severe pneumonia compared to those who were exclusively breastfed. In conclusion, exclusive breastfeeding plays an important role in reducing the risk of severe pneumonia among toddlers. It is expected that these findings can serve as a basis for healthcare workers to enhance education for mothers on the importance of exclusive breastfeeding.